Accumulation of armadillo induced by wingless, dishevelled, and dominant-negative zeste-white 3 leads to elevated DE-cadherin in Drosophila clone 8 wing disc cells. - Yanagawa, S.; Lee, J.S.; Haruna, T.; Oda, H.; Uemura, T.; Takeichi, M.; Ishimoto, A. (Journal of Biological Chemistry, 1997)
Drosophila genetic studies suggest that in the Wingless (Wg) signaling pathway, the segment polarity gene products, Dishevelled (Dsh), Zeste-white 3 (ZW-3), and Armadillo (Arm), work sequentially; wg and dsh negatively regulate zw-3, which in turn down-regulates arm. To biochemically analyze interactions between the Wg pathway and Drosophila E-cadherin (DE-cadherin) which bind to Arm, we overexpressed Dsh, ZW-3, and Arm, in the Drosophila wing disc cell line, clone 8, which responds to Wg signal. Dsh overexpression led to accumulation of Arm primarily in the cytosol and elevation of DE-cadherin at cell junctions. Overexpression of wild-type and dominant-negative forms of ZW-3 decreased and increased Arm levels, respectively, indicating that modulation in zw-3 activity negatively regulates Arm levels. Overexpression of an Arm mutant with an amino-terminal deletion elevated DE-cadherin levels, suggesting that Dsh-induced DE-cadherin elevation is caused by the Arm accumulation induced by Dsh. Moreover, the Dsh-, dominant-negative ZW-3-, and truncated Arm-induced accumulation of DE-cadherin protein was accompanied by a marked increase in the steady-state levels of DE-cadherin mRNA, suggesting that transcription of DE-cadherin is activated by Wg signaling. In addition, overexpression of DE-cadherin elevated Arm levels by stabilizing Arm at cell-cell junctions.